2023
DOI: 10.3390/microbiolres14040111
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Co-Infection in Patients with Coronavirus: A Rapid Review to Support COVID-19 Antimicrobial Prescription

María Fernanda Celaya Corella,
Jorge Omer Rodeles Nieblas,
Donato Antonio Rechy Iruretagoyena
et al.

Abstract: The goal of this study was to determine the most common microorganisms present in COVID-19 patients with co-infections at the General Hospital of Mexicali. Bacterial co-infections have been reported in two previous global pandemics caused by viruses. In a retrospective observational study, we obtained information from 1979 patients. All had symptoms of respiratory disease, and we performed real-time Polymerase Chain Reaction tests on nasopharyngeal swab samples. Of the 1979 patients, 316 were negative; so, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The study of Celaya Corella et al [13] set out to identify the most prevalent bacteria found in COVID-19 patients at the General Hospital of Mexicali. In the two previous worldwide pandemics brought on by viruses, bacterial co-infections have been documented.…”
mentioning
confidence: 99%
“…The study of Celaya Corella et al [13] set out to identify the most prevalent bacteria found in COVID-19 patients at the General Hospital of Mexicali. In the two previous worldwide pandemics brought on by viruses, bacterial co-infections have been documented.…”
mentioning
confidence: 99%